Risk factors, prevention, and repair strategies for tube erosion and exposure following glaucoma drainage device surgery: a narrative review - Narita, Akiko (Annals of Eye Science, 2026)
Background and Objective: Glaucoma drainage device (GDD) surgery is widely accepted as an alternative to trabeculectomy, including as a primary procedure. Tube erosion and exposure are rare but clinically significant complications with a substantial risk of endophthalmitis, often requiring repeat surgical intervention. The aim of this review was to synthesize existing data on the incidence, etiology, risk factors, preventive strategies, and treatment options for tube erosion or exposure, and discuss current strategies to optimize long-term outcomes following GDD surgery.Methods: A review of peer-reviewed English-language literature was conducted to identify studies addressing tube erosion and exposure following GDD surgery. Eligible studies included clinical research articles, meta-analyses, case series, and case reports. The literature search encompassed publications from the database inception up to and including August 31, 2025, with PubMed as the primary database and supplemented by searches of the Semantic Scholar corpus. Non-English publications, non-peer-reviewed articles, conference abstracts, and irrelevant publications were excluded.Key Content and Findings: Increased erosion risk is influenced by patient-related risk factors (age, sex, ethnicity, prior ocular surgery, inflammation, and neovascular or uveitic glaucoma) and surgery-related factors (combined procedures and tube location). Preventive strategies, particularly scleral tunnel techniques and double-thickness pericardium patch grafts, have yielded lower erosion rates. Successful repair strategies emphasize correcting the underlying cause of exposure through secure tube fixation, appropriate tube rerouting or repositioning, durable graft coverage, conjunctival reconstruction, and optimization of wound-healing conditions.Conclusions: Tube erosion and exposure remain multifactorial complications of GDD surgery, arising from patient-related, ocular, and surgical factors. Current evidence supports a mechanistic approach focused on minimizing tube micro-movement and mechanical stress at the conjunctival interface to prevent and repair tube erosion and exposure, rather than focusing solely on the graft material. Despite numerous proposed risk factors and surgical techniques, preventive and repair approaches remain unstandardized, reflecting the lack of validated risk assessment criteria and high-quality comparative evidence. Future research should prioritize consistent outcome reporting, multicenter studies, mechanistic studies linking clinical findings to tissue responses, and well-designed comparative trials to guide evidence-based prevention and management.